Teritorijas plānošanas problēmas Rīgas pilsētas un rajona administratīvajā teritorijā vides aizsardzības aspektā. - Jaška, Andrejs (Latvijas Universitāte, 2010)
Darbā tiek izskatīts jautājums par Rīgas pilsētas un Rīgas rajona administratīvās teritorijas plānošanas problēmām. Rīga ir ar augstāko iedzīvotāju blīvumu un rūpniecības infrastruktūru valstī. Darbā galvenā uzmanība ir pievērsta sekām, ko varētu radīt videi, viens no svarīgākajiem dokumentiem - Rīgas attīstības plāna (2006-2018) realizācija. Izskatīti mērķus un darbības jomas, kas noteiktas Rīgas attīstības plānā saistībā ar starptautiskajiem un nacionālajiem vides aizsardzības mērķiem un starptautiskajām saistībām, un Rīgas pilsētas atbilstību tām. Darbā tiek izskatītas arī vairākas juridiskās lietas, kurās parādās nevēlēšanās dažu normatīvo aktu atbilstību prasībām, klaji tās ignorējot no vides aizsardzības prasību puses. Izstrādājot bakalaura darbu radušies vairāki secinājumi, kas darba gaitā, apkopojot datus, analizēti darba nodaļās: 1) Ir pietiekami daudz normatīvo aktu vides aizsardzības, ekonomiskās un sociālās interešu jomā lai panāktu līdzsvaru. Kā arī vides aizsardzības mērķi ir iekļauti normatīvajos aktos, kas saistīti ar teritorijas plānošanas līmeņiem. 2) Pilsētas un lauku pašvaldības cenšas nodrošināt ekonomisko interešu aizsardzību plānošanas dokumentos, tīši un nelikumīgi ignorējot vides aizsardzības interesēs. 3) Ir nepieciešams pastiprināt kontroli pār procesu attīstības teritorijas plānu un uzraudzību, kuras veic atbildīgās valsts institūcijas, kas izslēdz iespēju attīstīt nelikumīgu teritorijas plānus un ignorējot tās atbilstību vides aizsardzības normu prasībām. Atslēgvārdi: Teritorijas plānošanas problēmas, vides aizsardzība, Rīgas attīstības plāns, Rīgas pilsētas un rajona teritorija.

The thesis considers Latvian normative acts and documents formulating the principle of development sustainability which is important for the development of the environment and the state. As well it tracks down how the basic principles of development sustainability are introduced in the basic principles of regional politics, regulating them legally. The thesis considers Riga city and Riga region administrative territory planning problem, and as it is the region with the highest figures for population density and industry infrastructure, the processes taking place here are the brightest example to reflect the processes taking place in the state as a whole. The thesis focuses on the consequences that might be caused to the environment by one of the most important documents in the state – Riga development plan (2006 - 2018). The compliance of objectives and activities specified in Riga development plan with international and national environment protection objectives and international obligations of Riga city is also analysed. The thesis also considers several legal cases caused by the reluctance of some Riga region municipalities (Garkalne rural municipality and Adaži rural municipality) and Riga City Council to comply with the requirements of the normative acts ignoring the environmental protection requirements in the process of planning. The following conclusions were drawn in the course of work summarising the data analysed in the sections of the thesis: 1) There is enough of legal regulations stipulated by the normative acts for putting environment protection, economic and social interests in balance, as the environmental protection objectives are included in all levels of normative acts related to territory planning. 2) City and rural municipalities are trying to ensure the protection of economic interests in the planning documents, wilfully and illegally ignoring the environment protection interests. 3) It is necessary to strengthen the control over the process of developing territory plans and monitoring performed by the responsible state institutions, which would exclude the possibility of developing illegal territory plans and ignoring its’ compliance with the requirements of environment protection norms. Keywords: administrative territory planning problems, environmental protection, the development plan of Riga, the Riga City and District area.
Spatial planning problems Riga city and district administrative territory environmental protection issues aspect.
Keywords: Juridiskā zinātne